The Implementation of the Problem-Based Learning Model in Teaching National Values - Novita Indrisari Lumban Gaol (PT. Mifandi Mandiri Digital, 2023)
Classroom Action Research (CAR) is conducted to address learning issues. A professional teacher must be able to apply various teaching models and learning media. The majority of students consider Civic Education to be the most boring subject. The purpose of this study is to evaluate the success of Classroom Action Research conducted by Civic Education teachers. This research employs a qualitative method. Data collection is carried out through observation, interviews, documentation, and literature review. The results of this study indicate that Civic Education teachers who implemented Classroom Action Research successfully addressed learning issues, such as low student motivation and performance, while also demonstrating that Classroom Action Research is a concrete solution to learning problems, particularly in Civic Education. The data collection included observations, questionnaires, and trials. In this study, the subjects were 15 eighth-grade students and 1 Civic Education teacher, with the assistance of the Problem-Based Learning model. The results show that the implementation of the Problem-Based Learning model effectively improved students' understanding in Civic Education lessons. Prior to using the Problem-Based Learning model, the average score was 47.8, and after its implementation, students' average scores improved to 75.4.